Letter from Max Bredig to Ernst Cohen, January, 1939 - Bredig, Max Albert (1939)
Letter from Max Albert Bredig (1902-1977) to Ernst Cohen (1869-1944) containing financial information that proves Max can support his father during his stay in the Netherlands.
Keywords: Bredig, Max Albert, 1902-1977; Cohen, Ernst, 1869-1944; Bredig, Georg, 1868-1944; Emigration and immigration; Chemists